1989
DOI: 10.1111/j.1752-1688.1989.tb03060.x
|View full text |Cite
|
Sign up to set email alerts
|

PRESERVATION OF SAMPLES FOR DISSOLVED MERCURY1

Abstract: Water samples for dissolved mercury require special treatment because of the high chemical mobility and volatility of this element. Widespread use of mercury and its compounds has provided many avenues for contamination of water. Two laboratory tests were done to determine the relative permeabilities of glass and plastic sample bottles to mercury vapor. Plastic containers were confirmed to be quite permeable to airborne mercury, glass containers were virtually impermeable. Methods of preservation include the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 30 publications
0
1
0
2
Order By: Relevance
“…A review of methods for preserving water samples concluded that plastic sample bottles are highly permeable to mercury dissolved in water, whereas glass containers are essentially impermeable. 27 Permeability of oxygen, moisture, and light through food packaging materials may have some relevance to this research. Glass and metals provide the greatest protection, whereas plastics generally offer less protection, with permeability depending on the type of plastic.…”
Section: Discussionmentioning
confidence: 99%
“…A review of methods for preserving water samples concluded that plastic sample bottles are highly permeable to mercury dissolved in water, whereas glass containers are essentially impermeable. 27 Permeability of oxygen, moisture, and light through food packaging materials may have some relevance to this research. Glass and metals provide the greatest protection, whereas plastics generally offer less protection, with permeability depending on the type of plastic.…”
Section: Discussionmentioning
confidence: 99%
“…Kombinasi asam nitrat dan kalium dikromat berhasil mengawetkan merkuri dalam berbagai konsentrasi dan bentuk terlarut. Karena pengawet asam-oksidan ini bertindak sebagai penampung merkuri di udara dan wadah plastik permeabel terhadap uap merkuri, botol kaca lebih disukai untuk pengumpulan sampel (Hamlin, 1989).…”
Section: Pendahuluanunclassified
“…L-Cysteine disarankan untuk digunakan bersama dengan HNO 3 sebagai pengawet larutan standar merkuri (Hamlin, 1989;Mladenova, Dakova, Tsalev, & Karadjova, 2012). Matriks cair menggunakan metode CVAAS menggunakan 10 mg L-Cysteine per liter air, sedangkan untuk matriks padatan (metode thermal decomposition) menggunakan 100 mg L-Cysteine per liter air.…”
Section: Pendahuluanunclassified